Pelajar Pancasila Pada Abad Ke-21 Di SMAN 1 Palangka Raya - Maryam Aulia; Misnawati Misnawati; Apritha Apritha; Reni Adi Setyoningsih; Putri Handayani; Winda Saptaniarsih (Universitas 45 Surabaya, 2023)
Education plays a big role in making students to preserve Pancasila as the entity and identity of the Indonesian nation. The purpose of this study is to determine the challenges and efforts of schools in realizing Pancasila as the entity and identity of the Indonesian nation. This research is a descriptive qualitative research with the subject of students X-5 and X-7 SMAN 1 Palangka Raya and the object of research is school policy in realizing Pancasila as the entity and identity of the Indonesian nation. Data collection was done through observation and documentation and analyzed by reducing data, presenting results and drawing conclusions. The results of this study are the challenges faced in the 21st century in the form of excessive use of technology and access to information that is not properly filtered will disrupt the focus of students in learning. The efforts made by the school are to create students characterized by Pancasila values through an independent curriculum and the implementation of the Pancasila learner profile. The implementation is carried out in the P5 (Pancasila Learner Profile Strengthening Project) learning process so that students will get used to it because the education paradigm in the 21st century makes the learning process in favor of students and makes students adaptable to adapt to the challenges of development in the 21st century. Therefore, the efforts made by the school have tried their best through the Pancasila learner profile as the entity and identity of the Indonesian nation in the 21st century.